2021
DOI: 10.3389/fonc.2021.538174
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Anti-PD-1/PD-L1 Monotherapy or Combinational Therapy in Patients Aged 75 Years or Older: A Study-Level Meta-Analysis

Abstract: Recent trials have shown a promising anti-tumor activity for advanced cancer patients treated with PD-1/PD-L1 inhibitors; however, little is known on the use of PD-1/PD-L1 inhibitors in adults over 75 years of age. Here, we performed a study-level meta-analysis to compare the efficacy of anti-PD-1/PD-L1 agents between elderly (≥ 75 years) and non-elderly (< 75 years) patients. In the present study, we systematically reviewed phase 2/3 trials of PD-1/PD-L1 inhibitors of advanced solid tumors that reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Clinical data on ICI efficacy in elderly individuals with cancer are encouraging but inconclusive, with retrospective meta-analyses showing similar or improved efficacy in aged (> 60 years) versus young (< 60 years) melanoma patients treated with ICI agents, [14][15][16][17][18] while another study showed no significant progression free survival (PFS) improvement in cancer patients ≥ 75 years of age treated with ICI versus control groups, while younger patients (< 75 years) had significant PFS improvement. 19 Despite contradictory data, age-related differences likely occur, but clinical studies could be underpowered due to low enrollment of elderly adults into clinical trials 20 or age effects on ICI in humans do not manifest until ages greater than those thus far studied.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data on ICI efficacy in elderly individuals with cancer are encouraging but inconclusive, with retrospective meta-analyses showing similar or improved efficacy in aged (> 60 years) versus young (< 60 years) melanoma patients treated with ICI agents, [14][15][16][17][18] while another study showed no significant progression free survival (PFS) improvement in cancer patients ≥ 75 years of age treated with ICI versus control groups, while younger patients (< 75 years) had significant PFS improvement. 19 Despite contradictory data, age-related differences likely occur, but clinical studies could be underpowered due to low enrollment of elderly adults into clinical trials 20 or age effects on ICI in humans do not manifest until ages greater than those thus far studied.…”
Section: Introductionmentioning
confidence: 99%
“…was based on eight trials involving patients treated with anti-PD-1/PD-L1. 60 The study showed that except for melanoma, anti-PD-1 and PD-L1 did not benefit elderly patients aged ≥75 years in terms of PFS and OS. Another meta-analysis of 34 studies by Huang et al.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, two meta-analyses addressed the efficacy of ICIs between age <75 and ≥75 years. 60 , 61 The meta-analysis by Nie et al. was based on eight trials involving patients treated with anti-PD-1/PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that in most studies the cut off age is 65 with only a small number of studies addressing the older population -75 and over (17-20), though the results for this age group seem to be comparable if not superior to those of patients younger than 75. This seems to be the case mainly in Melanoma as a meta-analysis published by Nie et al (21) has shown lower response rate for patients over 75 in comparison to younger patients with other types of solid tumors. The authors hypothesis for the difference between Melanoma and other tumor types is based on a study published by Samstein et al in 2019 which showed that Melanoma patients over 75 have a higher tumor mutational burden (TMB) when compared to other tumor types of the same age group (22).…”
Section: Introductionmentioning
confidence: 94%
“…This seems to be the case mainly in Melanoma as a meta-analysis published by Nie et al. ( 21 ) has shown lower response rate for patients over 75 in comparison to younger patients with other types of solid tumors. The authors hypothesis for the difference between Melanoma and other tumor types is based on a study published by Samstein et al.…”
Section: Introductionmentioning
confidence: 94%